Recognizing objects appeared in dangerous region in front of vehicles mounted computer vision system - Le, Mỹ Hà (Journal of Technical Education Science, 2019)
Today, the rapid growth of the new techniques has brought machines close to people. There are many applications that have positive results in our life, especially in autonomous vehicle and collision warning or avoidance. In this article, the authors proposed a method using a computer vision system mounted on moving vehicle to detect the objects appeared in the dangerous region to warning for a collision. The proposed method applied Aggregate Channel Features (ACF) to identify motorbikes and cars in different urban roads. In addition, the author combined lane detection using the bird-eyes view transformation algorithm and estimated the distance from the camera to other objects to support frontal warning. The result showed that this proposed method is an efficient technique with simplicity and fast processing speeds.